High-Level Carbapenem Resistance among OXA-48-Producing Klebsiellapneumoniae with Functional OmpK36 Alterations: Maintenance of Ceftazidime/Avibactam Susceptibility - Pilar Lumbreras-Iglesias; María Rosario Rodicio; Pablo Valledor; Tomás Suárez-Zarracina; Javier Fernández (MDPI AG, 2021)
The aim of this work was to analyze outer membrane porin-encoding genes (ompK35 and ompK36) in a collection of OXA-48 producing Klebsiella pneumoniae, to assess the effect of porin alterations on the susceptibility to ceftazidime/avibactam, and to describe a screening methodology for phenotypic detection of OXA-48-producing K. pneumoniae with disrupted porins. Antimicrobial susceptibility was tested by Microscan and Etest. The genomes of 81 OXA-48-producing K. pneumoniae were sequenced. MLST, detection of antimicrobial resistance genes, and analysis of ompK35 and ompK36 were performed in silico. Tridimensional structures of the OmpK36 variants were assessed. Receiver operating characteristics curves were built to visualize the performance ability of a disk diffusion assay using carbapenems and cefoxitin to detect OmpK36 functional alterations. A wide variety of OmpK36 alterations were detected in 17 OXA-48-producing K. pneumoniae isolates. All displayed a high-level meropenem resistance (MIC ≥ 8 mg/L), and some belonged to high-risk clones, such as ST15 and ST147. Alterations in ompK35 were also observed, but they did not correlate with high-level meropenem resistance. All isolates were susceptible to ceftazidime/avibactam and porin alterations did not affect the MICs of the latter combination. Cefoxitin together with ertapenem/meropenem low inhibition zone diameters (equal or lower than 16 mm) could strongly suggest alterations affecting OmpK36 in OXA-48-producing K. pneumoniae. OXA-48-producing K. pneumoniae with porin disruptions are a cause of concern; ceftazidime/avibactam showed good in vitro activity against them, so this combination could be positioned as the choice therapy to combat the infections caused by this difficult-to-treat isolates.